Coexistence of Craniovertebral Junction Stenosis with Pancake Kidney in an Adolescent with Acromesomelic Dysplasia - Gueven, Ayla; Dagcinar, Adnan; Ceyhan, Mellem (Freund Publishing House Ltd, 2008)
…